2013
DOI: 10.1128/jb.01512-12
|View full text |Cite
|
Sign up to set email alerts
|

The Sakaguchi Reaction Product Quenches Phycobilisome Fluorescence, Allowing Determination of the Arginine Concentration in Cells of Anabaena Strain PCC 7120

Abstract: The filamentous cyanobacterium Anabaena fixes nitrogen in specialized cells called heterocysts. The immediate product of fixation, ammonia, is known to be assimilated by addition to glutamate to make glutamine. How fixed nitrogen is transported along the filament to the 10 to 20 vegetative cells that separate heterocysts is unknown. N-fixing heterocysts accumulate an insoluble polymer containing aspartate and arginine at the cell poles. Lockau's group has proposed that the polymer is degraded at the poles to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…). This dipeptide appears to be an important vehicle for the transfer of nitrogen from heterocysts to vegetative cells, consistent with the possible existence of a gradient of arginine or an arginine‐containing compound in the diazotrophic filament (Ke and Haselkorn ). These results imply an active catabolism of arginine (and aspartate) in the vegetative cells of the diazotrophic filament.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…). This dipeptide appears to be an important vehicle for the transfer of nitrogen from heterocysts to vegetative cells, consistent with the possible existence of a gradient of arginine or an arginine‐containing compound in the diazotrophic filament (Ke and Haselkorn ). These results imply an active catabolism of arginine (and aspartate) in the vegetative cells of the diazotrophic filament.…”
Section: Discussionsupporting
confidence: 63%
“…As described in the Introduction, we have recently found that in the diazotrophic filament of Anabaena, the second step of cyanophycin degradation, hydrolysis of b-aspartyl-arginine, takes place mainly in vegetative cells (Burnat et al 2014). This dipeptide appears to be an important vehicle for the transfer of nitrogen from heterocysts to vegetative cells, consistent with the possible existence of a gradient of arginine or an arginine-containing compound in the diazotrophic filament (Ke and Haselkorn 2013). These results imply an active catabolism of arginine (and aspartate) in the vegetative cells of the diazotrophic filament.…”
Section: Discussionsupporting
confidence: 62%
“…Although the exact equation of intercellular nutrient exchange in the diazotrophic Anabaena filament is unknown, movement of sucrose, glutamate, and alanine from vegetative cells to heterocysts and of glutamine and β-aspartyl-arginine from heterocysts to vegetative cells could result in a net transfer of reduced carbon to heterocysts and of fixed nitrogen to vegetative cells. A possible gradient of arginine or of an argininecontaining compound in the diazotrophic filament of Anabaena has been noted (19).…”
Section: Discussionmentioning
confidence: 99%
“…Cyanophycin synthesis after nitrogen fixation has been suggested to serve an important function by removing from solution the products of nitrogen fixation, which could have a negative feedback effect on nitrogenase (18)(19)(20). Interestingly, this strategy appears to be generally used in nitrogen-fixing cyanobacteria independently of whether they are unicellular (36) or filamentous (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation